Розвиток передмість Ізмаїла у середині XIX ст. - Гулянович, І.М. (Культура народов Причерноморья, 2013)
In the mid–nineteenth century Izmail consisted from three parts: the fortress, the central part and the
suburbs. The article tell about of the suburbs of Izmail. Izmail’s suburbs were the settlements in the urban land.
There were Baranovka, Goncharovka, Kapkaz, Kopanaya Balka, Broska, Kugurluy, Larzhanka, Safiyany,
Matroska (Matrosskaya Sloboda), Staraya Nekrasovka and Novaya Nekrasovka. Inhabitants of these
communities were engaged in agriculture, viticulture, animal husbandry, fishing. tendencies in the settlement
area settlements, socio–economic development and land use, the formation of social, ethnic and religious
composition of the population in the mid–nineteenth century. Among suburbs of Izmail of the most distinguished
Staraya Nekrasovka and Novaya Nekrasovka. Inhabitants were Russian Old Believers (Nekrasovites) and
differed from the Orthodox Ukrainians and Moldovans. After failing for the Russian Empire East war of 1853–
1856 Izmail’s suburbs became part of the Principality of Moldavia. В статті розглянуто особливості розвитку передмість Ізмаїлу. Досліджені тенденції в
заселенні території поселень, соціально–економічному розвитку й землекористуванні, формування
соціальної сфери, етнічному і конфесійному складі населення у середині ХІХ ст. В статье рассмотрено особенности развития пригородов Измаила. Исследованы
тенденции в заселении территории поселений, социально–экономическом развитии и землепользовании,
формировании социальной сферы, этническом и конфессиональном составе населения в середине ХІХ в.